Two bullets in the gun: combining immunotherapy with chemotherapy to defeat neuroblastoma by targeting adrenergic-mesenchymal plasticity - D’Amico, Silvia; Tempora, Patrizia; Gragera, Paula; Król, Kamila; Melaiu, Ombretta; De Ioris, Maria Antonietta; Locatelli, Franco; Fruci, Doriana (Frontiers in Immunology, 2023)
Neuroblastoma (NB) is a childhood tumor that originates in the peripheral sympathetic nervous system and is responsible for 15% of cancer-related deaths in the pediatric population. Despite intensive multimodal treatment, many patients with high-risk NB relapse and develop a therapy-resistant tumor. One of the phenomena related to therapeutic resistance is intratumor heterogeneity resulting from the adaptation of tumor cells in response to different selective environmental pressures. The transcriptional and epigenetic profiling of NB tissue has recently revealed the existence of two distinct cellular identities in the NB, termed adrenergic (ADRN) and mesenchymal (MES), which can spontaneously interconvert through epigenetic regulation. This phenomenon, known as tumor plasticity, has a major impact on cancer pathogenesis. The aim of this review is to describe the peculiarities of these two cell states, and how their plasticity affects the response to current therapeutic treatments, with special focus on the immunogenic potential of MES cells. Furthermore, we will discuss the opportunity to combine immunotherapy with chemotherapy to counteract NB phenotypic interconversion.